THE ROLE OF TURQUOISE MINE IN MIDDLE ASIA (American Journal of Business Management, Economics and Banking, 2023)
This article talks about the turquoise mine located in the ancient Ilaq and its place in the civilization in the formation and gradual development of the Central Asian civilization. In addition, scientific research and views of many archaeologists and scientists on the study of the mining and mining industry in the regions are presented in order of importance.